Pro-Tumor and Anti-Tumor Functions of IL-17 and of TH17 Cells in Tumor Microenvironment - Gulubova M. (Sciendo, 2016)
The current review reveals the seven subclasses of CD4+ T helper cells, i.e. Th1, Th2, Th9, Th17, Th22, regulatory T cells and Tfh, the cytokines produced by them and their role in tumor microenvironment. Main attention was paid to IL-17 and Th17 cells. IL-17-producing cells were described, among which were Treg17 cells and Tc17 cells. The transcription factors, engaged in the activation of Th17 cell differentiation were reviewed. It was shown that Th17 cells might possess regulatory functions in tumor microenvironments that directs toward immunosuppression. The reciprocity between Treg and Th17 cells is realized when the production of a large amount of TGF-β in tumors causes Treg cell differentiation, and the addition of IL-6 shifts the differentiation of naïve T cells to Th17 cells. The main pro-tumor role of IL-17 is the promotion of tumor angiogenesis through stimulation of fibroblasts and endothelial cells. The antitumor functions of IL-17 are associated with enhancement of cytotoxic activity of tumor specific CTL cells and with angiogenesis that provide channels through which immune cells might invade tumor and promote antitumor immunity.